Ergonomičke odrednice odnosa operator- stroj - radna sredina u edukaciji djelatnika u zračnom prometu - Grozdanić, Berislav (Promet - Traffic&Transportation, 2012)
Education of operators in air, road and rail transport is particularly significant for traffic safety. It. can generally be divided in to three stages (selection, theoretical and practical part, and training in the course of service). Numerous are the factors affecting the efficiency of an operator, while ergonomy being part of industrial psychology gives answers to the essential issues and measures for the elimination of adverse effects in operators. . The modern school and university system as well as the economic system of the Republic of Croatia have been meeting the world standards in operator education by way of the scientifically grounded training of manpower. It is necessary to find common grounds in education of operators in all segments of the transport industry.